Elite soccer players do not cover less distance in the second half of the matches when game interruptions are considered - Rey, E.; Kalén, A.; Lorenzo-Martínez, M.; López-Del Campo, R.; Nevado-Garrosa, F.; Lago-Peñas, C. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to analyze quantitative differences in the physical demands of male elite soccer players between the first and second halves during official matches, accounting for effective playing time (the duration of play after subtracting the game interruptions) and playing positions. A total of 4,249 individual match observations of 412 outfield players competing in the Spanish first division league (LaLiga) were undertaken during the 2018-2019 season, using a computerized tracking system (TRACAB, Chyronhego, New York, NY). The players were classified into 5 positional roles: central defenders (CD), external defenders (ED), central midfielders (CM), external midfielders (EM), and forwards (F). The main results showed that in contrast to those observed when total playing time was considered, independent of playing position, there were no significant differences on high-speed running (HSR) (5.5 ± 2.4 vs. 5.5 ± 2.4 m·min-1) and sprint (5.3 ± 3.3 vs. 5.4 ± 3.3 m·min-1) distances between the first and second halves in professional soccer players when the effective playing time was considered. However, differences in match running performance at HSR and sprint distances between the first and second halves were dependent on players' playing position. Whereas ED and EM maintained HSR and sprint efforts during the second half, CD and CM significantly increased (p < 0.001) the distance covered at sprint during the second period of the match. Contrarily, F were unable to maintain their HSR (6.2 ± 2.3 vs. 5.9 ± 3.3 m·min-1) and sprint (7.0 ± 3.5 vs. 6.5 ± 3.4 m·min-1) match running performances during the second half. Such findings demonstrate that total playing time could overestimate fatigue-induced performance declines. Thus, effective playing time and playing position should be taken into account when interpreting the match running performance of professional soccer players.